Comparing and contrasting barriers in augmentative alternative communication use in nonspeaking autism and complex communication needs: multi-stakeholder perspectives - Yau, Shu H.; Choo, Kaylynn; Tan, Jane; Monson, Olivia; Bovell, Stephanie (Frontiers in Psychiatry, 2024)
Augmentative alternative communication (AAC) devices or systems are often prescribed to minimally verbal or nonspeaking autistic individuals and other individuals with complex communication needs to facilitate communication or as an alternative to spoken language. AAC use can result in communication gains and improved quality of life for minimally verbal or nonspeaking individuals. Despite this, AAC abandonment is high, limiting societal participation of the individual on the autism spectrum with complex communication needs. Our study is a novel exploration of the barriers of AAC use from a multi-stakeholder perspective, and a qualitative analysis of similarities and differences between stakeholders. We conducted semi-structured interviews and focus groups with 30 parent-carers, educators and clinicians currently supporting AAC users in Western Australia and analysed the data using reflexive thematic analysis. Barriers from each stakeholder group were coded, resulting in 17 subthemes forming five main themes common to all stakeholders: Stakeholder Knowledge, Stakeholder Attitudes and Stigma, Resources, AAC User Engagement, and Device Fit. Contrasting perspectives included actual and perceived stigma associated with AAC use (parent-carers vs clinicians); different struggles with resources and knowledge (parent-carers vs clinicians and educators); and a lack of clinician communication in the processes that determined AAC-fit for school environments (educators only). Findings are discussed in the context of improving inter-stakeholder collaboration and capacity building in Australian health service and practice to better support minimally verbal or nonspeaking autistic individuals and individuals with complex communication needs. Suggestions are also offered for communication partner training.